Specters of democracy blackness and the aesthetics of politics in the antebellum U.S. - Wilson, Ivy G. (New York ; Oxford : Oxford University Press, 2011)
This text interrogates the representational strategies that 19th-century Americans used in art and literature to delineate blackness as an index to the forms of US citizenship. The book reveals how the task of representing African Americans in imaginative expression was part of a larger dilemma concerning representative democracy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: American literature -- African American authors -- History and criticism; African Americans in literature; Democracy in literature; Nationalism in literature; African American authors -- Political and social views; Discourse analysis, Literary; Rhetoric -- Political aspects -- United States -- History